SIRAH LEARNING MOBILE APPLICATION FOR KAFA PRIMARY SCHOOL STUDENTS: A PRELIMINARY STUDY - Siti Fatimah Mohd Rum; Nurulhuda Basri; Azlin Dahlan (Journal of Islamic, Social, Economics and Development, 2022)
Sirah is one of the Malaysian Islamic education systems for Ujian Penilaian KelasKAFA (UPKK) subject compulsory for all primary students in Standard 5. Due to the Covid-19 pandemic, teachers have to cancel most classes and opt for online classes. Thus, the biggestissue arose when the students found it challenging to focus on online lectures because they werein an undesigned classroom and would miss class if their internet connection was poor. Inaddition, they had difficulties memorizing the subjects if they were not appropriately engaged.As a result, this research offered a new learning technique utilizing the interactive Sirahlearning mobile application. Students will read notes and take quizzes on three introductorytopics in Sirah based on the KAFA syllabus. The ADDIE model was used to design and developthis mobile application, which runs on Android. Functionality testing results showed that thisstudy achieved its requirements, and using SUS calculation, usability testing established a goodscore of 77.81%. In conclusion, this approach may enable students to learn more enjoyable andconveniently without worrying about missing classes.